PENERAPAN PERMAINAN KARTU BERGAMBAR DALAM UPAYA PENINGKATAN KOSAKATA - I Gusti Bagus Wahyu Nugraha Putra; Made Yogi Marantika; I Made Perdana Skolastika (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2018)
ABSTRACT This research is designed in form of action-based research which involved four steps in each circle, namely planning, action, observation and reflection. Before treatment, pre-test is conducted in other to know the students’ ability at the beginning. So, the achievement can be compared to the next circle. Circle I consisted of four sessions; three sessions for conducting actions and one session administering post-test I. Circle II consisted of three sessions; two sessions for conducting actions and one session for post-test II. The aim of this research is to know the implementation of flash card game through vocabulary mastery of disabled students at Yayasan Bakti Senang Hati. This research is conducted at Yayasan Bakti Senang Hati which some disabled students are used as the subject of the research. It used seven kategories of vocabulary such as animal, family, fruits, number, things, vegetables and part of body as the instrument in colleting the data. The result of data showed that the use of flash card game could improve the vocabulary mastery of disabled students at Yayasan Bakti Senang Hati. It can be seen from the result of the students’ achievement tests which increased continuously during the application of the technique. During the pre-test, students are able to master 17 vocabularies from each category. Then, after the first Cilcle test there are 13 vocabularies form each category that they got. Therefore, their mastery became 30 vocabularies. Finnaly, it became 59 after the result of second cicle is held. Key words: vocabulary, flash card, implementation